Service productivity in different industries – an empirical investigation. Issue 2 (2nd March 2015) - Klingner, Stephan; Pravemann, Stephanie; Becker, Michael
Abstract : Purpose: – The purpose of this paper is to quantitatively evaluate of the current status of productivity management of industrial and non-industrial service companies in Germany. Based on that knowledge, best practices and needs regarding tools and methods can be identified. Design/methodology/approach: – In two qualitative pre-studies the theoretical foundation of service productivity was built. Using this knowledge, a quantitative empirical survey was conducted, including almost 2000 service companies. The sampling frame was based on a company database provided by Hoppenstedt. Samples were randomly selected using proportionate stratified sampling. Findings: – The findings show the economic importance and meaningfulness of service productivity management, independently from the industry. Research limitations/implications: – Due to the chosen population, the findings are limited to Germany. Furthermore, a more detailed comparison of service industries beyond industrial and non-industrial services was not feasible. Practical implications: – The data contained evidence that companies conducing productivity management are more successful than those who are not. This underlines the economic importance service productivity management. Originality/value: – The paper provides reliable, quantitative insights of the current status, demands, and benefits of service productivity management in the industrial as well as non-industrial sector.